Perceived stress and career planning awareness of Japanese and Taiwanese undergraduate dental hygiene students - Shin-Ru Liao; Naoko Seki; Masako Akiyama; Kayoko Shinada; Ikuko Morio (Elsevier, 2023)
Background/purpose: Dental hygiene students' stress might be rising with increasing undergraduate study content and expansions in dental hygienists' roles and expectations as society changes. This study explored Japanese and Taiwanese dental hygiene students' perceptions of stress and their idea of career planning. Materials and methods: Participants were second- to fourth-year students in the 2020 academic year at Tokyo Medical and Dental University (TMDU; n = 60) and Taipei Medical University (TMU; n = 62). An anonymous questionnaire was distributed, which included questions on demographic information and career planning, as well as the Perceived Stress Scale-10 (PSS-10) and modified Dental Environment Stress questionnaire (DES). Results: The response rates were 100.0% (TMDU) and 96.8% (TMU). The number of participants who chose dental hygiene as the first program choice (P < 0.001) and wished to work as dental hygienists after graduation (P = 0.018) in TMDU was significantly higher than in TMU. There was no significant difference between the two schools' stress levels in both PSS-10 and DES-26. The factors influencing students who wished to work as dental hygienists after graduation were "clinical year or not" (P = 0.007) in TMDU, and the DES factor included items related to lack of confidence in becoming a successful and competent dental hygienist, expectations, and fear of the future (P = 0.033) in TMU. Conclusion: Both schools' students experienced moderate or relatively low levels of stress. TMDU students had higher stress related to academic studies, while TMU students had slightly higher stress related to future anxiety.